Evaluation and Tasks of the Legal System on the Program on the Promotion of Education of Critical Foreign Languages - Ho Kim (International Journal of Advanced Culture Technology(IJACT), 2025)
This study analyzes the Act on the Promotion of Education of Critical Foreign Languages and the Program on the Promotion of Education of Critical Foreign Languages. The ‘Act on the Promotion of Education of Critical Foreign Languages’ enacted in 2016 established a structural and financial foundation for supporting education and research in critical foreign languages. The ‘Program on the Promotion of Education of Critical Foreign Languages’ is being implemented as a means to realize the Act. This study evaluates the process and status of enactment and revision of the Act, and the composition and progress of the program to confirm the status of implementation of the Act. Through this evaluation, this study aims to present the challenges the Act on the Promotion of Education of Critical Foreign Languages faces and to seek ways to improve it.